Effects of a Phone-Based Support Program for Women With Breast Cancer Undergoing Chemotherapy: A Pilot Study - Xi Chen PhD candidate, RN; Nujjaree Chaimongkol PhD, RN; Pornpat Hengudomsub PhD, RN (SAGE Publishing, 2024)
Introduction The increasing number of women with breast cancer undergoing chemotherapy may result in long-lasting, adverse physical side effects and reduced quality of life. Objective This study aimed to develop and assess the feasibility and preliminary effects of the Phone-Based Support Program for women with breast cancer undergoing chemotherapy. The primary outcome was self-care self-efficacy; secondary outcomes were symptom distress and quality of life. Methods This pilot study was conducted at a tertiary hospital in Jiangsu province, China, from February to March 2023. The Phone-Based Support Program was delivered to 20 participants through the smartphone application WeChat, consisting of learning, discussion, ask-the-expert, and personal stories components. Outcome measures were assessed at three time points: preintervention, postintervention, and follow-up. Results The Phone-Based Support Program was feasible and could improve self-care self-efficacy, decrease symptom distress, and promote quality of life. The program was well-accepted, and participants engaged actively in the online discussion and sought expert advice. Conclusions The Phone-Based Support Program showed feasibility and effectiveness in improving self-care self-efficacy, reducing symptom distress, and enhancing quality of life.